INTEGRATED STRATIGRAPHY FROM THE CONTRADA FORNAZZO SECTION, MONTE INICI, WESTERN SICILY, ITALY: PROPOSED G.S.S.P. FOR THE BASAL BOUNDARY OF THE TITHONIAN STAGE - GIULIO PAVIA; ROBERTO LANZA; FRANCESCA LOZAR; LUCA MARTIRE; FEDERICO OLÓRIZ; ELENA ZANELLA (Rivista Italiana di Paleontologia e Stratigrafia, 2004)
This paper deals with a definition of the lower boundary stratotype of the Tithonian Stage in the Upper Jurassic succession of Monte Inici, Western Sicily. The upper member of the Rosso Ammonitico Fm. is 27 m thick and shows a typical nodular-calcareous lithofacies; its lower beds have been sampled for biostratigraphic and paleomagnetic purposes. Though the succession is affected by high stratigraphic condensation, the resulting hiatuses have been shown to be below biochronological resolution and thus do not hinder any biostratigraphic definition. The biostratigraphic analysis has been based on the rich ammonite assemblages in which the common genus Hybonoticeras is the index-key for characterizing the Kimmeridgian-Tithonian boundary. Four ammonite biozones have been identified; the basal Tithonian one is defined by the assemblage of Hybonoticeras gr. hybonotum and Haploceras staszycii. The recorded calcareous nannofossil bioevents allow recognition of the V. stradneri and C. mexicana Zones, whose boundary is located a little below the identified Tithonian lower boundary. The paleomagnetic record shows normal polarity in the S. darwini/V. albertinum Zone and mainly reverse polarity in the H. beckeri and H. hybonotum Zones, with three minor normal polarity intervals; the lower boundary of the Tithonian falls in the oldest of these intervals. The integrated multidisciplinary stratigraphic information gathered from the Contrada Fornazzo section defines the lower boundary of the H. hybonotum Zone at the base of Bed 110, and supplies elements of chrono-correlation sufficient to regard this section as a possible G.S.S.P. of the Tithonian Stage.